Using Truncated Test for Finding the Parameters of Single Sampling Plan under Distribution of Log-Logistic - عبود سهيل نجم; اسماعيل بيداء (Journal of Economics and Administrative Sciences, 2012)
A group of acceptance sampling to testing the products was designed when the life time of an item follows a log-logistics distribution. The minimum number of groups (k) required for a given group size and acceptance number is determined when various values of Consumer’s Risk and test termination time are specified. All the results about these sampling plan and probability of acceptance were explained with tables.